Formononetin: a review of its source, pharmacology, drug combination, toxicity, derivatives, and drug delivery systems - Jin, Min; Wei, Linfang; Wang, Jianhua; Shen, Yuehong; Gao, Lei; Zhao, Fan; Gao, Qianying; Ma, Yifei; Sun, Yongyan; Lin, Ying; Ji, Guanjie; Cai, Pingping; et al. (Frontiers in Pharmacology, 2025)
Formononetin (FMN) is a common natural metabolite that can be extracted and isolated from some common botanical drugs. In recent years, FMN has garnered increasing attention due to its beneficial biological activities. In this paper, we systematically summarize the sources of FMN and provide a comprehensive review of its pharmacological activities and molecular mechanisms, co-administration, toxicity, derivatives, and drug delivery systems in the last 5 years. The study results found that FMN has a wide range of pharmacological activities in neurological disorders, organ damage and cancer, showing great potential for clinical application and broad prospects. Researchers are exploring various types of delivery systems, including nanoparticle carriers, ligand modifications and polymer microspheres. These advanced delivery systems can enhance the stability of FMN, prolong its release time in vivo, and improve targeting, thereby optimizing its therapeutic efficacy and reducing side effects, and greatly improving its bioavailability. In conclusion, FMN is a natural metabolite with considerable research value, and its diverse biological activities make it a promising candidate for drug development and medical research.